An eXtended EDFM approach to modeling fracture evolution in coupled THMC processes during CO2 storage and geo-energy development - Qizhi Tan; Shuyang Liu; Junchao Li; Senhu Lin; Zhiqiang Wang; Junrong Liu; Yanji Wang; Baojiang Sun (Journal of Cleaner Production, 2026)

Activation energy and organic matter structure characteristics of shale kerogen and their significance for the in-situ conversion process of shale oil - Wenxue Han; Xia Luo; Shizhen Tao; Senhu Lin; Jinzhong Liu; Yanting Yang (Fuel, 2024)

An experimental investigation into the elastic and thermal properties of oil shales: Yanchang formation, Ordos basin - Senhu Lin; Hui Li; Xia Luo; Yan Zhang; Lijun Zhang (Marine and Petroleum Geology, 2023)

Heat-Induced Pore Structure Evolution in the Triassic Chang 7 Shale, Ordos Basin, China: Experimental Simulation of In Situ Conversion Process - Zhongying Zhao; Lianhua Hou; Xia Luo; Yaao Chi; Zhenglian Pang; Senhu Lin; Lijun Zhang; Bo Liu (Journal of Marine Science and Engineering, 2023)
The reservoir properties of low–medium-maturity shale undergo complex changes during the in situ conversion process (ICP). The experiments were performed at high temperature (up to 450 °C), high pressure (30 MPa), and a low heating rate (0.4 °C/h) on low–medium-maturity shale samples of the Chang 7 Member shale in the southern Ordos Basin. The changes in the shale composition, pore structure, and reservoir properties during the ICP were quantitatively characterized by X-ray diffraction (XRD), microscopic observation, vitrinite reflectance (Ro), scanning electron microscopy (SEM), and reservoir physical property measurements. The results showed that a sharp change occurred in mineral and maceral composition, pore structure, porosity, and permeability at a temperature threshold of 350 °C. In the case of a temperature > 350 °C, pyrite, K-feldspar, ankerite, and siderite were almost completely decomposed, and organic matter (OM) was cracked into large quantities of oil and gas. Furthermore, a three-scale millimeter–micrometer–nanometer pore–fracture network was formed along the shale bedding, between OM and mineral particles and within OM, respectively. During the ICP, porosity and permeability showed a substantial improvement, with porosity increasing by approximately 10-times and permeability by 2- to 4-orders of magnitude. Kerogen pyrolysis, clay–mineral transformation, unstable mineral dissolution, and thermal stress were the main mechanisms for the substantial improvement in the reservoir’s physical properties. This study is expected to provide a basis for formulating a heating procedure and constructing a numerical model of reservoir properties for the ICP field pilot in the Chang 7 shale of the Ordos Basin.

Sedimentary features of the gravity flow influenced shale deposit: A case study of Chang 7 member in the Ordos Basin, China - Lianhua Hou; Zhenglian Pang; Xia Luo; Senhu Lin (Marine and Petroleum Geology, 2023)

Geochemical characteristics of the source rocks in Mesozoic Yanchang formation, central Ordos Basin - Senhu Lin; Xuanjun Yuan; Shizhen Tao; Zhi Yang; Songtao Wu (Journal of Earth Science, 2013)